Application potential of solar-assisted post-combustion carbon capture and storage (CCS) in China: A life cycle approach. (15th June 2017) - Wang, Junyao; Zhao, Jun; Wang, Yongzhen; Deng, Shuai; Sun, Taiwei; Li, Kaixiang
Abstract: Although post-combustion carbon capture (PCC) has been regarded as a near-commercial technology, the scale-up development of PCC the technology remains hindered by its severe thermodynamic and economic penalties. As a consequence, the solar-assisted carbon capture and storage (CCS) technology is emerging recently, which poses a promising possibility to offset the power generation loss caused by the intensive energy consumption from PCC process. Nevertheless, the application potential of the solar-assisted CCS technology would highly depend on its realistic greenhouse gas (GHG) mitigation benefit as well as its cost relative to alternative low carbon technologies. Thus, it is required to apply an improved assessment practice to recognize solutions for such sustainable power supply chains, considering an increasing threatening from climate change. In this study, solar-assisted post-combustion CCS processes are analyzed trough a life cycle approach, combing life cycle GHG assessment and life cycle cost analysis. A typical 300MWe coal-fired power plant in China is taken as the case study. Three scenarios are further analyzed: (1) base case integrated with CCS process; (2) base case integrated with CCS and solar-assisted reboiler heating process; (3) base case extended to CCS and solar-assisted repowering process. Results show that the solar-assisted repowering case has considerable advantage in both GHG mitigation potential and cost aspect with superior life cycle GHG reduction rate and life cycle cost of energy removed (LCOR) at 73.7% and 37.2/ t c o 2 − e q respectively. While the solar-assisted reboiler heating case does not have evident competition superiority. It is further highlighted that the GHG emissions from the upstream and transportation stages are also critical for Chinese CCS chains.